The Effects of Instagram-Based Information Dissemination and the Perceived Green Value on Z-Generation’s Interest in Thrifting - Muhimmatul Ifadah; Ana Madinatul Ilmi; Virza Utama Alamsyah; Gede Herry Arum Wijaya (Yayasan Ilomata, 2023)
In recent years, sustainable development in various fields has grown significantly. The consumption on environmentally-friendly and ecologically-safe products becomes the major concern, one of which is through a thrifting activity among youth. In addition, a number of earlier researches focusing on the significant impact on a social media platform, particularly Instagram, that promotes the green consumption practices have been conducted . The aim of this study is to investigate how information related to the support of green awareness on social media such as Instagram encourages the thrifting purchase among Z Generation to occur. The dual mediating function of perceived green values and subjective norms is investigated in this study. A questionnaire using a Google Form filled up by 165 respondents from Z Generation in Indonesia was distributed. The results were as follows: (1) Sharing green-value related information on Instagram has a positive effect on thrifting purchase intentions; (2) The perceived green values and The subjective norms are detected as a mediating role in the thrifting behaviors. The findings from the study not only enrich empirical research on Z Generation's thrifting activity, but also assist experts to develop methodologies to drive the intentions and to set up the behavior of the Z Generation on the thrifting practice itself. Furthermore, the results may trigger small-scale businesses to strategize their products sales so as to boost thrifting among Generation Z consumers.